PSYCHOLOGICAL AND PEDAGOGICAL FOUNDATIONS FOR ESTABLISHING AN INTEGRATIVE E-LEARNING ENVIRONMENT IN ENERGY-RELATED TECHNICAL EDUCATION (Scientific journal of the Fergana State University, 2025)
This article explores the psychological and pedagogical underpinnings of designing an e-learning environment for teaching technical subjects in energy-focused higher education. Drawing on key theories of motivation and cognitive development, we outline how integrative instructional strategies-combining problem-based tasks, collaborative activities, and technology-enhanced resources-can foster core competencies among students. A pilot study employing both quantitative and qualitative methods illustrates how appropriately structured digital tools and instructional models positively impact learners’ motivation, engagement, and conceptual understanding. Emphasis is placed on aligning curricular objectives with students’ cognitive needs and professional readiness for the energy sector. The findings demonstrate that a well-conceived e-learning framework, grounded in solid pedagogical principles, not only supports deeper knowledge acquisition but also encourages active participation and self-directed learning habits. This work offers practical recommendations for educators aiming to enhance student outcomes in technical disciplines through a research-informed, psychologically responsive, and pedagogically sound electronic learning environment.